2020
DOI: 10.31910/rudca.v23.n1.2020.1178
|View full text |Cite
|
Sign up to set email alerts
|

El cromo-levadura y la ractopamina afectan el perfil de ácidos grasos y la calidad de la carne en cerdos

Abstract: como la ractopamina modifican características de la carne, como la dureza y el perfil de ácidos grasos. Palabras clave: retención de agua; carcasa; grasa dorsal; pérdidas por goteo; resistencia al corte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…These results are consistent with those reported by other studies that compared the effects of dietary organic Cr and RAC supplementation in finishing pigs [ 42 , 43 , 44 ]. Furthermore, Mayorga et al reported that the addition of organic Cr (CrProp) in the diets of pigs reared under heat stress conditions exerted positive effects on the ADG and final BW [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those reported by other studies that compared the effects of dietary organic Cr and RAC supplementation in finishing pigs [ 42 , 43 , 44 ]. Furthermore, Mayorga et al reported that the addition of organic Cr (CrProp) in the diets of pigs reared under heat stress conditions exerted positive effects on the ADG and final BW [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…RAC increased the FA C20:46 content (p < 0.05), consistent with the findings of Trujillo et al, who observed changes in the concentration of PUFA in the meat of pigs supplemented with 10 ppm RAC and 0.4 mg organic Cr/kg of food [44]. Furthermore, Jin et al and Tian et al supplemented 0.2 mg CrMet/kg of food in the diet of pigs and reported that the concentration of arachidonic acid in the meat of pigs supplemented with CrMet did not change following the treatment [63,64].…”
Section: Chemical Compositionsupporting
confidence: 91%
See 1 more Smart Citation